Assessing the resurgent irrigation development program of the Philippines: Synthesis report - Arlene B. Inocencio; Albert Dale Inocencio (Philippine Institute for Development Studies (PIDS), 2020)
This paper synthesizes the results and findings of four component studies under the resurgent irrigation development assessment: the technical and institutional assessments of national and communal irrigation systems, the water resource assessment and the governance components. This synthesis is structured according to the research questions posed to the component studies along the project cycle. The first two components provided technical and institutional evaluations of selected NIS and CIS systems from Luzon to Mindanao from project identification, to preparation, appraisal, and selection, to project implementation, operations maintenance, and monitoring and evaluation. The water resources component assessed the irrigation service areas as originally planned or designed compared to the actual service areas with respect to water availability, land use (including flood vulnerability) and status of irrigation facilities. The governance component discussed and analyzed the governance mechanisms for the irrigation sector and the irrigation project from planning to monitoring and evaluation.
Keywords: 330; technical and institutional assessments; irrigation management; water policy; water governance; national irrigation systems; communal irrigation systems